(untitled) (AGROINNOVATSIYА, 2024)
Ross-308 and Cobb-500 broiler chickens were crossed with local Kulangi (dakang) roosters to raise first-generation chicks from two different crosses. This article provides recommendations for the care of agricultural poultry